Artificial Intelligence as a Catalyst for Transforming Learning in Higher Education - Achariya, Amara (PT. Batari Edu Calya, 2025)
The rapid advancement of digital technology has significantly influenced educational practices, particularly within higher education. Among these innovations, Artificial Intelligence (AI) has emerged as a powerful tool that reshapes pedagogical strategies, administrative processes, and student learning experiences. This article examines the transformative role of AI in higher education through a systematic review of recent literature published between 2018 and 2024. The findings highlight four main dimensions of AI adoption: adaptive learning systems, learning analytics, virtual assistants, and administrative automation. These applications enhance personalization, teaching efficiency, assessment quality, and accessibility. However, challenges such as limited infrastructure, digital competence gaps, ethical dilemmas, and the digital divide persist as major barriers to effective implementation. The discussion emphasizes that AI’s integration into higher education extends beyond technological efficiency; it represents a paradigm shift toward inclusive, data-driven, and future-oriented learning environments. The article concludes that higher education institutions, particularly in Southeast Asia, must invest in infrastructure, faculty training, and regulatory frameworks to maximize AI’s potential while safeguarding educational equity and integrity.